The Taste of Emotion: How Food Quality and Cafe Atmosphere Quality Shape Revisit Intention Through Positive Emotion - Rahmaniar, Desi; Listiana, Erna; Sulistiowati, Sulistiowati; Afifah, Nur; Setiawan, Harry (Economic Reviews Journal, 2026)
The growth of the cafe industry in Indonesia, including in the city of Pontianak, continues to increase in line with changes in people's lifestyles, with cafes serving as social and recreational spaces. Increasingly fierce competition between cafes requires businesses to enhance both food quality and cafe atmosphere quality to create customer experiences that foster revisit intentions. This study was conducted to analyze the effect of food quality and cafe atmosphere quality on revisit intention through positive emotion among customers of Chatting Cafe in Pontianak City. This study also used an explanatory quantitative approach using an S-O-R framework. Data were collected through a structured questionnaire adapted from previous studies, involving 206 respondents obtained using purposive sampling techniques. Data analysis was performed using PLS-SEM with the help of SmartPLS 4.0. The results of this study show that there is a positive and significant influence of food quality and cafe atmosphere quality on positive emotion. Additionally, positive emotion has a positive and significant effect on revisit intention. However, food quality and cafe atmosphere quality are not proven to have a significant direct effect on revisit intention. However, food quality and cafe atmosphere quality were not found to have a significant direct effect on revisit intention. Furthermore, the results confirmed that positive emotion significantly mediated the effect of food quality and cafe atmosphere quality on revisit intention.